La Grande Guerre patriotique : narrations sociales et monuments de guerre - Bouchard, Michel (Anthropologica, 2013)
War monuments are abundant in Russia; they are part of the landscape, while defining the terrain. Calling to the past and bringing forth memories, they define belonging, com memorating the past while shaping the future. Remembering a war is a political act and, in remembering, we define our place in our community, country and the world. Such is the case in Eastern Europe and Russia whose territories have been invaded many times over the centuries, which has led to development of a selective memory, the "curation" of the nation. This article explores memories of Russia to demonstrate how monuments and museums of war define the past, present and dreams for the future.